2006
DOI: 10.1007/11758549_58
|View full text |Cite
|
Sign up to set email alerts
|

Survive Under High Churn in Structured P2P Systems: Evaluation and Strategy

Abstract: Abstract. In Peer to Peer (P2P) systems, peers can join and leave the network whenever they want. Such "freedom" causes unpredictable network environment which leads to the most complex design challenge of a p2p protocol: how to make p2p service available under churn? What is more, where is the extreme of a system's resistibility to high churn? A careful evaluation of some typical peer-to-peer networks will contribute a lot to choosing, using and designing a certain kind of protocol in special applications. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…Value area of Churn is between 0.1 and 0.5. 0.5 is a critical value with which system will collapse in a short time [26]. Let C present SSE individual availability, then its temporary offline probability is B= (1-C) × (1-A) (1).…”
Section: B Stochastic Petri Network Modelmentioning
confidence: 99%
“…Value area of Churn is between 0.1 and 0.5. 0.5 is a critical value with which system will collapse in a short time [26]. Let C present SSE individual availability, then its temporary offline probability is B= (1-C) × (1-A) (1).…”
Section: B Stochastic Petri Network Modelmentioning
confidence: 99%
“…The authors reported that these DHTs can achieve similar performance, if they are correctly calibrated. In [17], the authors measured the level of churn that different DHT topologies can tolerate. They used a random-failure churn model in order to find the churn level that yields a successful lookup ratio greater than 0.5.…”
Section: B Related Workmentioning
confidence: 99%
“…DHTs can be adapted to handle Byzantine faults [17,36,38,63], and the problem of churn has also been ad- 7 We also assume global knowledge in one of our applications (AShare, §4.2), but this assumption is not inherent in Atum. dressed in [54,60]. Tentative lookup schemes that are both secure and churn-friendly are given in [74], where session times as low as 10 minutes are theoretically explored.…”
Section: Related Workmentioning
confidence: 99%